Nuclear Stiffness Decreases with Disruption of the Extracellular Matrix in Living Tissues. Issue 6 (20th January 2021) - McCreery, Kaitlin P.; Xu, Xin; Scott, Adrienne K.; Fajrial, Apresio K.; Calve, Sarah; Ding, Xiaoyun; Neu, Corey P.
Abstract: Reciprocal interactions between the cell nucleus and the extracellular matrix lead to macroscale tissue phenotype changes. However, little is known about how the extracellular matrix environment affects gene expression and cellular phenotype in the native tissue environment. Here, it is hypothesized that enzymatic disruption of the tissue matrix results in a softer tissue, affecting the stiffness of embedded cell and nuclear structures. The aim is to directly measure nuclear mechanics without perturbing the native tissue structure to better understand nuclear interplay with the cell and tissue microenvironments. To accomplish this, an atomic force microscopy needle‐tip probe technique that probes nuclear stiffness in cultured cells to measure the nuclear envelope and cell membrane stiffness within native tissue is expanded. This technique is validated by imaging needle penetration and subsequent repair of the plasma and nuclear membranes of HeLa cells stably expressing the membrane repair protein CHMP4B‐GFP. In the native tissue environment ex vivo, it is found that while enzymatic degradation of viable cartilage tissues with collagenase 3 (MMP‐13) and aggrecanase‐1 (ADAMTS‐4) decreased tissue matrix stiffness, cell and nuclear membrane stiffness is also decreased. Finally, the capability for cell and nucleus elastography using the AFM needle‐tip technique is demonstrated. These results demonstrate disruption of the native tissue environment that propagates to the plasma membrane and interior nuclear envelope structures of viable cells. Abstract : The nucleus is a mechanosensing organelle that bears mechanical loads propagated from the extracellular matrix, impacting gene expression. After tissues are enzymatically disrupted, an atomic force microscopy technique is applied to measure stiffness of the cell membrane and nuclear envelope while cells are viable and still embedded in their native tissue environment.